Projek Perancangan Reaktor Asap Cair Dalam Skala Labolatorium Di Laboratorium Energi Terbarukan : Analisa Konsistensi Produk - tamja, usriana; meji, asni (LENVARI, 2024)
This research focuses on the liquid smoke reactor, also known as a pyrolysis reactor. It is a device used in the production of liquid smoke from biomass materials. The pyrolysis process occurs when biomass is heated in the absence of oxygen or with very limited oxygen. As a result, chemical breakdown of polymers into simpler monomers or components takes place. The reactor is designed using stainless steel material with a diameter of 30 cm and a height of 40 cm. The bottom of the reactor is conical in shape. Additionally, the reactor is connected to a condenser via pipes to condense the vapor produced during the pyrolysis process into liquid smoke. Other components in this pyrolysis apparatus include a gas collector and a combustion chamber, which work together to produce liquid smoke from biomass. Under operational conditions, the maximum temperature achieved is 200°C. The operating time to produce charcoal ranges from 4 to 5 hours, depending on the raw material used, such as tea waste, cassava peel, or a mixture of tea waste and cassava peel. The maximum charcoal formation achieved is approximately 80%. By extending the operating time to 8-9 hours using raw materials like coconut shells, coffee grounds, or a combination of coconut shells and coffee grounds, there is an additional 10% increase in charcoal formation. Thus, the overall charcoal formation ratio reaches 90%.